Are counter movement jump and isometric mid-thigh pull tests reliable, valid, and sensitive measurement instruments when performed after maximal cardiopulmonary exercise testing? A sex-based analysis in elite athletes - Pojskić, Hari; Schiller, Jesper; Pagels, Peter; Ragnarsson, Thony; Melin, Anna K. (Frontiers in Physiology, 2025)
Both the countermovement jump (CMJ) and the isometric mid-thigh pull (IMTP) are frequently used performance tests to monitor neuromuscular fatigue and recovery after exhaustive physical activities. However, to date, neither the reliability nor the validity of the CMJ and IMTP performed after the cardiopulmonary exercise testing (CPET) has been studied. Thus, this study primarily aimed to investigate the intrasession relative and absolute reliability of the CMJ and IMTP when performed after the CPET. Second, the study aimed to examine the discriminative validity of the CMJ and IMTP performed after the CPET by differentiating between elite male and female athletes. Twenty-eight female (26.8 ± 6.6 years) and seventeen male (23.8 ± 3.5 years) elite Swedish athletes voluntarily participated in the study. Protocols included anthropometric measurements, a cycle ergometer-based CPET (i.e., VO2peak test), followed by three maximal test-retest CMJ and IMTP trials. Jump height, peak power, and relative peak power during CMJ and peak force and relative peak force during IMTP testing were analysed. Results showed high relative reliability of the CMJ and IMTP in the total sample (ICC: 0.97 and 0.98) and separately in male (ICC: 0.88 and 0.98) and female (ICC: 0.98 and 0.93) athletes. The good absolute reliability of the CMJ and IMTP was evidenced by low within-subjects test-retest variability (CVWS%) and typical measurement error percentage, ranging between 5.7% and 6.5% and 6.3% and 8.9%, respectively. Both the CMJ and IMTP showed good test sensitivity, with the smallest worthwhile change exceeding the typical error. The CMJ’s jump height, relative peak power, and IMTP’s peak force showed a large discriminatory capacity to differentiate between male and female athletes (Cohen’s d = 3.92, 1.80 and 5.14, respectively). However, when the peak force was standardised relative to body mass and lean mass, the differences between sexes diminished. In conclusion, given that the CMJ and IMTP tests demonstrated high reliability and sensitivity following CPET, they could be confidently used as practical tools for monitoring neuromuscular fatigue and recovery, even after exhaustive cardiopulmonary exertion activities. Additionally, the demonstrated discriminative validity in differentiating between male and female athletes further supports their role in sex-specific performance profiling.